Time dependence of free fall gravity drainage in unconsolidated sand - Iglauer, Stefan; Muggeridge, A. (Begell House, 2012)
The time dependence of the gravity drainage of brine through a water wet porous medium has been examined experimentally using continuous resistance measurements in three 1 m columns packed with sand. Analysis of the resulting data showed that water saturation at any particular location had a power law dependence on time. This was shown to be consistent with gravity-dominated drainage and the fact that the water relative permeability can be described by the Corey parameterization. This confirmed earlier analyses which showed that gravity-dominated drainage should have a power law dependence on time.